THE APPLICATION OF GOOD FAITH IN CONTRACTS DURING A FORCE MAJEURE EVENT AND BEYOND WITH SPECIAL REFERENCE TO THE COVID-19 ACT 2020 (UUM Journal of Legal Studies, 2023)
Many parties face difficulties in performing contracts due to the economic dislocation since the outbreak of COVID-19. The extraordinary nature of this pandemic situation calls for good faith in contractual settings. The discussion of this paper focuses on the imposition in a force majeure event which will cause many contracts to be unenforceable. The research method used doctrinal analysis to discuss the force majeure clause in the context of the COVID-19 pandemic and the obligation of good faith in contracts. This paper will discuss the COVID-19 pandemic as a force majeure event, arguing that the rise of "good faith" in contract law and the application of "good faith" in contracts as a mitigation for a force majeure event. The paper will then present its conclusion and recommendations. The findings highlight the significance of applying "good faith" in the event of force majeure and beyond as a mitigating factor in alleviating uncertainty and unfairness.